Pengaruh Multy Sensory Marketing Terhadap Niat Berkunjung Kembali Konsumen Coffee Shop Bun Kopi Unila - Miftahhudin; Dwi Asri Siti Ambarwati (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the simultaneous and partial effects of Multy Sensory Marketing (Sight, Smell, Taste, Sound, and Touch) on consumer revisit intention at Bun Kopi Unila Coffee Shop. The research employs a quantitative explanatory approach with 100 respondents selected through purposive sampling. Data were gathered through questionnaires and analyzed using multiple linear regression via SPSS 25. The partial tests show that Sight, Taste, and Touch have a positive and significant effect, with Taste as the most dominant driver, whereas Smell and Sound have positive but non-significant effects. The five dimensions simultaneously explain 48.5% of revisit intention. Management is advised to maintain taste consistency, improve visual cleanliness, optimize air circulation, and apply a dayparting music strategy.